2021
DOI: 10.1155/2021/6712785
|View full text |Cite|
|
Sign up to set email alerts
|

An Efficient CNN for Hand X-Ray Classification of Rheumatoid Arthritis

Abstract: Hand Radiography (RA) is one of the prime tests for checking the progress of rheumatoid joint inflammation in human bone joints. Recognizing the specific phase of RA is a difficult assignment, as human abilities regularly curb the techniques for it. Convolutional neural network (CNN) is the center for hand recognition for recognizing complex examples. The human cerebrum capacities work in a high-level way, so CNN has been planned depending on organic neural-related organizations in humans for imitating its unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Furthermore, the metrical analysis demonstrated a clear change in the joint diameter/finger line ratio after successful therapy and resolution of inflammation. To our knowledge, this is the first application of CNNs to real-world images in the setting of RA or osteoarthritis, whilst in previous studies, CNNs were applied to radiographs and ultrasound images [11, 12]. Such a patient-controlled biomarker could complement patient reported outcomes and wearables and thus empower patients in monitoring their disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the metrical analysis demonstrated a clear change in the joint diameter/finger line ratio after successful therapy and resolution of inflammation. To our knowledge, this is the first application of CNNs to real-world images in the setting of RA or osteoarthritis, whilst in previous studies, CNNs were applied to radiographs and ultrasound images [11, 12]. Such a patient-controlled biomarker could complement patient reported outcomes and wearables and thus empower patients in monitoring their disease.…”
Section: Discussionmentioning
confidence: 99%
“…This automation of the bone erosion scoring process reduces the time and effort required for manual analysis by medical professionals, although it heavily depends on the quality and diversity of the training data. Additionally, a CNN architecture efficient for image classification tasks is proposed in Refs., 30,31 aiming to automate the classification process and assist radiologists in quickly identifying potential cases of RA from x-ray images. However, it is crucial to address imbalances in the dataset, as they can affect the model's performance and introduce biases toward the majority class.…”
Section: Related Workmentioning
confidence: 99%
“…A study found that building accurate models to forecast complex disease outcomes using electronic health record data is possible [15]. More recently, convolutional neural networks have become the dominant method for medical image classification [16,17], medical image segmentation [18]. An efficient CNN architecture (GRNN) achieves high accuracy for hand X-ray classification [19].…”
Section: Our Contributions To Wrist-joint X-ray Image Detectionmentioning
confidence: 99%